PENGEMBANGAN E-MODUL EKONOMI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH - Subagyo; Artantri, Martia Winda; Muchson, Mochamad (Universitas Nusantara PGRI Kediri, 2022)
Learning in schools can basically run well if all the supporting components of learning are able to make an impact or are able to achieve the objectives of the learning itself. Departing from this, this research seeks to develop learning media in the form of e-modules with the aim of being able to improve the quality of learning in the classroom so that learning objectives can be achieved. The research method used is the research and development method, with the research subject at MAN 1 Kediri and the research object, namely class X students. Stages in this development research consist of: 1) preliminary study; 2) identification of the problem; 3) preparation of e-modules; and 4) validation of e-modules to experts. The results of the study found that from the expert validators media the valid level was 3,49 with excellent qualifications, from material expert validators the validity level is 3,57 with excellent qualifications, and from the validity level language expert valids were 3,56 with excellent qualifications. So that the economic e-module developed is categorized as valid and worthy of use in learning.